A comparative study of differences between parents and teachers in the evaluation of environmental sensitivity - Costa-López, Borja; Ferrer-Cascales, Rosario; Ruiz-Robledillo, Nicolás; Albaladejo-Blázquez, Natalia; Baryła-Matejczuk, Monika (Frontiers in Psychology, 2023)
The inextricable bond between humans and the environment underscores the pivotal significance of environmental sensitivity. This innate trait encompasses a wide array of ways individuals perceive, process, and react to various internal and external stimuli. The evaluation of this trait in children is generally conducted by parents. However, little is known about the concordance of the parents reports with those conducted by others, such as teachers. Children's behavior assessment is a current and relevant issue and finding out more positive results could make improvements in different contexts, such as home, clinics and schools. This study examines agreements and discrepancies between parents and teachers as raters of environmental sensitivity in Spanish children. Participants were 124 parents and eight teachers of youngsters between 3 and 10 years, who completed a paper survey providing information about parental and school variables and environmental sensitivity. Parents and teachers mostly differ when rating environmental sensitivity, being parents the raters who score higher levels of this trait than teachers. Also, poor intra-class coefficients of reliability are found in both the items of HSCS, the dimensions and the general factor of environmental sensitivity among the informants. The present investigation provides novel findings related to inter-rater assessment on environmental sensitivity and how these different informants could affect in the report. This study also highlights the need of making and validating new and specific tools to assess environmental sensitivity for teachers.